Magnetosonic wave-aided terahertz emission by nonlinear mixing of lasers in plasmas. (16th December 2019) - Kumar, Narender; Singh, Ram Kishor; Uma, R.; Sharma, R. P.
Abstract: A scheme of phase-matched terahertz generation by beating two co-propagating lasers in magnetized plasma, in the presence of a magnetosonic wave (MSW), is developed. The beat frequency ponderomotive force of the lasers imparts an oscillatory drift to electrons. The electron drift velocity couples with the electron density perturbation associated with the MSW to produce an irrotational nonlinear current $\left(\nabla × {\vec J}\;{}^{\rm NL}\ne 0\right)$ . The beat current density resonantly excites a THz (Terahertz) radiation when the phase-matching conditions are satisfied. The MSW mediates the phase matching. At 9.6 and 10.6 µm wavelengths, and background magnetic field of 285 kG, one may achieve normalized THz wave amplitude of the order of 10 −3 and one obtains the ratio of THz power to pump power of the order of 10 −6 .